Application of fluorescence melting curve analysis for dual DNA detection using single peptide nucleic acid probe. (18th February 2015) - Ahn, Jeong Jin; Lee, Seung Yong; Hong, Ji Young; Kim, Youngjoo; Kim, Gi Won; Hwang, Seung Yong
<x xml:space="preserve">Abstract</x> Peptide nucleic acid (PNA) is an artificially synthesized polymer. PNA oligomers show greater specificity in binding to complementary DNAs. Using this PNA, fluorescence melting curve analysis (FMCA) for dual detection was established. Genomic DNA of Mycoplasma fermentans and Mycoplasma hyorhinis was used as a template DNA model. By using one PNA probe, M. fermentans and M. hyorhinis could be detected and distinguished simultaneously in a single tube. The developed PNA probe is a dual‐labeled probe with fluorescence and quencher dye. The PNA probe perfectly matches the M. fermentans 16s rRNA gene, with a melting temperature of 72°C. On the other hand, the developed PNA probe resulted in a mismatch with the 16s rRNA gene of M. hyorhinis, with a melting temperature of 44–45°C. The melting temperature of M. hyorhinis was 27–28°C lower than that of M. fermentans. Due to PNA's high specificity, this larger melting temperature gap is easy to create. FMCA using PNA offers an alternative method for specific DNA detection. © 2015 American Institute of Chemical Engineers Biotechnol. Prog., 31:730–735, 2015